Pengaruh Subjective Norm dan Religiosity terhadap Purchase Intention dari Halal Brands Melalui Attitude - Alvin Refaldy; Rodhiah Rodhiah (Jurnal Ilmiah Ekonomi Islam, 2023)
The number of brands on the market makes every customer face in determining the product to be purchased. Products with Halal certification are very important for adherents of the Islamic faith. The broad perspective of Halal brands has become a component of life for a follower of Islam. In Indonesia, in the industry, it is necessary to have a halal status and must go through several procedural steps in order to be able to market the Halal brand. The existence of this study aims to examine the effect of subjective norms and religiosity on purchase intention and attitude as a medium for mediating subjective norms and religiosity on purchase intentions of Halal brands. The technique used is non-probability sampling with a purposive sampling method, then the questionnaire distributed online via google form, and processed using SmartPLS 4. The population is users of Halal brands, totaling 105 respondents domiciled in Jakarta. This research uses data analysis, such as validity and reliability tests; multicollinearity; coefficient of determination; effect size; and hypothesis testing. The results of this study are subjective norms and religiosity can affect purchase intention, while subjective norms and religiosity can affect purchase intentions through attitude mediation. Keywords : Subjective Norm, Religiosity, Attitude, Purchase Intention, Halal Brands